Investigating cold based summit glaciers through direct access to the glacier base: a case study constraining the maximum age of Chli Titlis glacier, Switzerland - Bohleber, Pascal; Hoffmann, Helene; Kerch, Johanna (The Cryosphere, 2018)
Cold glaciers at the highest locations of the European Alps have been investigated by drilling ice cores to retrieve their stratigraphic climate records. Findings like the Oetztal ice man have demonstrated that small ice bodies at summit locations of comparatively lower altitudes may also contain old ice if locally frozen to the underlying bedrock. In this case, constraining the maximum age of their lowermost ice part may help to identify past periods with minimum ice extent in the Alps. However, with recent warming and consequent glacier mass loss, these sites may not preserve their unique climate information for much longer. Here we utilized an existing ice cave at Chli Titlis (3030 m), central Switzerland, to perform a case study for investigating the maximum age of cold-based summit glaciers in the Alps. The cave offers direct access to the glacier stratigraphy without the logistical effort required in ice core drilling. In addition, a pioneering exploration had already demonstrated stagnant cold ice conditions at Chli Titlis, albeit more than 25 years ago. Our englacial temperature measurements and the analysis of the isotopic and physical properties of ice blocks sampled at three locations within the ice cave show that cold ice still exists fairly unchanged today. State-of-the-art micro-radiocarbon analysis constrains the maximum age of the ice at Chli Titlis to about 5000 years before present. By this means, the approach presented here will contribute to a future systematic investigation of cold-based summit glaciers, also in the Eastern Alps.
Gesehen am 13.04.2018